Experimental and theoretical investigations of the effect of bis-phenylurea-based aliphatic amine derivative as an efficient green corrosion inhibitor for carbon steel in HCl solution - Mohanad Shkoor (3768385) (2023)
A novel bis-phenylurea-based aliphatic amine (BPUA) was prepared via a facile synthetic route, and evaluated as a potential green organic corrosion inhibitor for carbon steel in 1.0 M HCl solutions. NMR spectroscopy experiments confirmed the preparation of the targeted structure. The corrosion inhibitory behavior of the prospective green compound was explored experimentally by electrochemical methods and theoretically by DFT-based quantum chemical calculations. Obtained results revealed an outstanding performance of BPUA, with efficiency of 95.1% at the inhibitor concentration of 50 mg L−1 at 25 °C. The novel compound has improved the steel resistivity and noticeably reduced the corrosion rate from 33 to 1.7 mils per year. Furthermore, the adsorption study elucidates that the mechanism of the corrosion inhibition activity obeys Langmuir isotherm with mixed physisorption/chemisorption modes for BPUA derivatives on the steel surface. Calculated Gibb's free energy of the adsorption process ranges from −35 to −37 kJ mol−1. The SEM morphology analysis validates the electrochemical measurements and substantiates the corrosion-inhibiting properties of BPUA. Additionally, the eco-toxicity assessment on human epithelial MCF-10A cells proved the environmental friendliness of the BPUA derivatives. Density functional theory (DFT) calculations correlated the inhibitor's chemical structure with the corresponding inhibitory behavior. Quantum descriptors disclosed the potentiality of BPUA adsorption onto the surface through the heteroatom-based functional groups and aromatic rings. Other Information Published in: Heliyon License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.heliyon.2023.e20254